2013
DOI: 10.1007/s00464-012-2611-y
|View full text |Cite
|
Sign up to set email alerts
|

Causes of dissatisfaction after laparoscopic fundoplication: the impact of new symptoms, recurrent symptoms, and the patient experience

Abstract: Dissatisfaction is uncommon after laparoscopic fundoplication. New symptoms, such as dysphagia and gas/bloating, are primary causes of dissatisfaction despite general reflux alleviation among these patients. New symptoms occur sooner after fundoplication than recurrent symptoms and may become less common with time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 38 publications
0
41
1
Order By: Relevance
“…Severe and persistent postoperative dysphagia after LTF is the main cause of reoperations in GERD´s surgical treatment, posing a major concern for the enthusiasts of this type of treatment (2,12,17) The proper investigation of this complication is mandatory for the adequate selection of the treatment. Well-positioned valves, without evidences of structural defects, can be adequately treated with endoscopic dilation as a first choice; nonetheless, patients with twisted, migrated or anatomically disrupted fundoplications rarely respond satisfactorily to endoscopic treatment and should be taken to early surgical correction (5) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe and persistent postoperative dysphagia after LTF is the main cause of reoperations in GERD´s surgical treatment, posing a major concern for the enthusiasts of this type of treatment (2,12,17) The proper investigation of this complication is mandatory for the adequate selection of the treatment. Well-positioned valves, without evidences of structural defects, can be adequately treated with endoscopic dilation as a first choice; nonetheless, patients with twisted, migrated or anatomically disrupted fundoplications rarely respond satisfactorily to endoscopic treatment and should be taken to early surgical correction (5) .…”
Section: Discussionmentioning
confidence: 99%
“…It provides good control of gastroesophageal reflux in the medium and long term (6,7,19,21) . However, the surgical approach of GERD is associated with several adverse effects, especially gas-bloating and dysphagia, that results in loss of quality of life and great dissatisfaction in significant proportion of patients (2,17) . Several randomized studies and their metaanalyses have demonstrated that routine short gastric vessels (SGV) division is not necessary in LTF and is associated with a greater occurrence of complications.…”
Section: Introductionmentioning
confidence: 99%
“…Among the complications we had one abscess of the abdominal wall, one ischemic stroke, one opening lung pleura (no need drainage) and one prolonged ileus with symptomatic abdominal distention. The mean hospital stay was 3 days 8,9,17,22,28,29,34,37,38 .…”
Section: Perioperative Datamentioning
confidence: 99%
“…Early dysphagia is defined as during the first six weeks after surgery and is a very common postoperative symptom which rarely requires some specific treatment. Persistent dysphagia beyond six weeks has been reported in 3-30% of patients 8,12,17,18,27,28,31,32,38 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation